Survey Minat Olahraga Petanque pada SMA & SMK - Utomo, Heru Puji; Nurhidayat, Nurhidayat; Syaukani, Agam Akhmad; Subekti, Nur (Jurnal Porkes, 2022)
This research is motivated by the lack of knowledge about petanque sport in Blora Regency, because petanque sport is a new sport in Blora Regency. Therefore, the researcher aims to find out the interest in petanque sports in students, especially at the high school / vocational level. This research method uses descriptive quantitative methods, data collection techniques are carried out by filling out questionnaires on a Likert scale 1-5 and processing data using SPSS version 22 software. The population of this study is all students of SMK Negeri 2 Blora, SMA Negeri 2 Blora, and SMK Negeri 1 Retreat. The samples of this study were two class X from each school of SMK Negeri 2 Blora, totaling 64 students, SMA Negeri 2 Blora totaling 64 students, and SMK Negeri 1 Kunduran totaling 50 students. So the number of samples from this study was 178 students. From the results of this study obtained data as many as 178 respondents. Around 61% of respondents know about the sport of petanque and the basic techniques of the game as well as the aspects contained in the game of petanque. In addition to knowledge about petanque sports, 35% of respondents have a desire to participate in petanque sports and 36% are motivated to play an active role in petanque sports. So it can be concluded that the research entitled Survey of Petanque Sports Interests in SMA/SMK in Blora Regency resulted in 35% of students having an interest in participating in petanque sports.